Identification of Genetic Variants in 65 Obesity Related Genes in a Cohort of Portuguese Obese Individuals - Ginete, Catarina (2021)
Funding: This research was funded by Instituto Politécnico de Lisboa by IDI&CA project IPL/2017/ genetobese/ESTeSL. Fundação Para a Ciência e Tecnologia, Portugal: FCT/MCTES (UIDB/05608/2020 and UIDP/05608/2020)–H&TRC.